DIPG-54. p53 pathway reactivation as a therapeutic strategy in diffuse intrinsic pontine glioma. (3rd June 2022) - Lupien, Leslie; Rendo, Veronica; Morin, Eric; Khuu, Nicholas; DiGiacomo, Jeromy; Khadka, Prasidda; Chacon, Madison; Lu, Sophie; Pelton, Kristine; Elcavage, Lara; Langhnoja, Jaldeep; Ligon, Keith; et al.
Abstract: TP53 is the most frequently mutated tumor suppressor with somatic alterations found in approximately 50% of all human cancers. In the remaining TP53 wild-type (WT) tumors, functional inactivation of the p53 pathway may be achieved through a variety of other mechanisms, including gene deletion, epigenetic silencing, and/or alterations in prominent negative regulators, including MDM2/MDM4 and PPM1D. These alterations block p53 activity and lead to uncontrolled cell proliferation and oncogenesis in a majority of cancers, including the highly aggressive, universally fatal glial cell tumors of childhood, known as Diffuse Intrinsic Pontine Gliomas (DIPGs). DIPGs are inoperable due to their location within the brainstem. Available treatment options, including radiotherapy, have had a palliative effect at best, with almost all children succumbing to the disease within 18 months of diagnosis. Recent advances have led to an improved understanding of the biological underpinnings of this disease and identification of recurrent genetic alterations that represent potential therapeutic targets for these patients. Prominent among these targets in DIPGs with WT p53 status (50%) are MDM2/4 and PPM1D, whose suppression lead to p53 reactivation specifically in the WT p53 context. We have undertaken a combination of approaches to better understand the therapeutic potential of MDM2 and PPM1D inhibition in DIPG, characterizing the genomic, transcriptomic, and cell-state changes that drive resistance, and identifying novel vulnerabilities that can be exploited with combination therapies towards a cure.